Short Message Services (SMS) Fraud Against Mobile Telephone Provider Consumer Review From Law Number 8 Of 1999 Concerning Consumer Protection - Novanema Duha (Journal of Law Science, 2021)
Technological advances, especially in the telecommunications sector, are growing very rapidly. One of the communication products/tools created is a cellular phone/mobile phone. The development of this technology does not rule out the possibility of fraudulent short message service (SMS) via cellular phones against consumers. The presence of Law Number 8 of 1999 concerning Consumer Protection as a form of protecting consumers against fraud via SMS. The problems raised in writing this thesis are how to protect the rights of consumers of cellular phone providers, then how to protect personal information and data of cellular phone provider consumers, and how to protect consumers from fraud through short message service (SMS). The research method used in writing this thesis is a normative juridical legal research method, namely by collecting data from various references either through books, legislation, websites, and other reference sources. Based on the results of the study, it is known that the rights of consumers of cellular phone providers refer to Law Number 8 of 1999 concerning Consumer Protection. While the protection of personal information and data is not specifically regulated, but partially regulated in Law Number 36 of 1999 concerning Telecommunications and Law Number 11 of 2008 concerning Information and Electronic Transactions. Furthermore, legal protection efforts for cellular phone provider consumers against fraud committed via SMS, can be in the form of preventive legal remedies and repressive legal remedies, and preventive actions can be taken for fraud through SMS.